The Contrast - Tyler, Royall, 1757-1826; McKee, Thomas Jefferson, 1840-1899 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Contrast" by Royall Tyler is an American play written in 1787. As the first professionally produced comedy by an American citizen, it satirizes Americans who embrace British fashions and customs over homegrown values. The plot centers on Maria Van Rough, promised to the Anglophile dandy Billy Dimple, who secretly pursues two other women while she finds herself drawn to the honorable patriot Colonel Manly. Through sharp wit and contrasting characters, Tyler explores the clash between European sophistication and American authenticity in the young nation. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Contrast_(play)
1st US Play Performed
Release date is 1996-06-01
Produced by Judith Boss
Keywords: Comedy plays; American drama (Comedy)